Cyberattacks/Incidents and Responding to Them - Kaczmarczyk, Barbara (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
The 21st century has brought forth the digital age. In the past, various types of activities and services could only be performed in the real world, and could be understood without computers. Currently, digital development has rendered possible the performance of numerous, if not almost all, everyday activities online. Services such as online shopping, booking trips, and opening bank accounts are also currently more financially profitable than traditional methods, as well as less time-consuming. Importantly, it is also possible to conduct elections and educational or product promotional campaigns via the Internet in today’s digital world, and to conduct fast, free searches for various different pieces of information and large datasets. Digitalisation has undoubtedly contributed to the development of many areas of human life, groups, and institutions. The development of civilization and the digital world also led to the rise of various mechanisms, such as incidents or cyberattacks, that can disrupt these processes. Some of the reasons underlying incidents or cyberattacks, which are highly varied, include achieving quick financial success and destabilising the functioning of specific groups or organisations. Therefore, it is very important to recognise how incidents or cyberattacks work and how to prepare for them, prevent them, and if they occur, how to respond to them. It is also important to restore the status to that before the occurrence of the incidents or the cyberattack.Research methodology: The article was developed based on Polish and international literature on the subject of security and cybersecurity, as well as Internet sources. During the research process, interviews with cybersecurity experts were conducted.Keywords: cyber incident, cyberattack, cybersecurity, cyber space, cyber defence